Navigating change: a qualitative exploration of chatbot adoption in recruitment - Aaradhana Rukadikar; Komal Khandelwal (Cogent Business & Management, 2024)
The human element in HR is challenging to replace. Although technology integration promises efficiency improvements, it also raises concerns about how it may affect employee engagement, interpersonal connections, and organisational culture. This study aims to shed insight into the complex environment surrounding chatbot adoption by clarifying the experiences of individuals navigating this revolutionary process. The study emphasises the value of efficient communication and integration by examining HR professionals' and recruiters' opinions of chatbots' reliability, privacy issues, organisational culture, and how they handle employee resistance to their adoption in hiring. With a focus on 25 HR professionals and recruiters, this study examines their experiences and challenges of integrating chatbots into the hiring process using a qualitative research design. While participant narratives are analysed by advanced tools like VOSviewer to provide insightful analysis, semi-structured interviews offer insights particular to the setting. This study on chatbots in hiring sheds light on the difficulties HR professionals encounter in the recruitment technology sector. Human resources professionals and recruiters concur that chatbots are transparent, trustworthy, and dependable. Strong data protection rules and open communication help to handle privacy and data security concerns.
Keywords: 650; Chatbot; artificial intelligence; recruitment; hR; qualitative study